PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII3 SMP NEGERI 8 PEKANBARU - Maya Anggraini; Putri Yuanita; Atma Murni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to improve learning process and to increase the mathematic learning evaluation by implying cooperative learning of Team Assisted Individualization. The subjects of this research are student in grade VIII3 of SMP Negeri 8 Pekanbaru at the second semester of academic year 2015/2016. Total number of participant are 36 whose academic achievement are heterogen. This research is a class action research which have two cycles, each cycle have four stages: planning, implementation, observation, and reflection. Each cycle closed by daily exam. The data collected by observation and examination at daily based. The data analised by narative descriptive analysis and statistical descriptive analysis. The implementation succes if the improvement of the learning process and the number of students reach minimum completeness criteria (MCC) increase at daily examination I and daily examination II. The research result from the observation form shows that teacher and student activity are better after the treatment implemented. More than half students actively participated in the learning process, as discuss, presented student worksheet (SW), responded to presenter group, and gave the learning conclusion. The students also tried to solve the quiz from teacher in a great manner. The number of students whose achieved basic score of MCC,; daily examination I (first cycle), and daily examination II (second cycle) are 11.11%, 83.33% and 80.55%. This research shows that cooperative learning of Team Assisted Individualization can improve learning process and increase mathematic learning evaluation for VIII3 of SMP Negeri 8 Pekanbaru.Key Words: Mathematical Achievement, Cooperative Learning, Cooperative Learning of Team Assisted Individualization